NEW RECOMMENDATIONS FOR THE MANAGEMENT OF RHEUMATOID ARTHRITIS (EULAR, 2013): THE ROLE OF METHOTREXATE - Evgeniy L Nasonov; D E Karateev; N V Chichasova (Научно-практическая ревматология)
In our previous publication, we reported the main provisions of the new EULAR recommendations (2013) and discussed some debating points of RA pharmacotherapy that require further research. The purpose of this article is to review the present-day knowledge concerning the use of methotrexate (MT), since according to the EULAR recommendations, “MT should be considered as the main component of the strategy of the first-line treatment of active RA”. In the context of EULAR recommendations, special priority was given to the discussion of MT administration in patients with early inflammatory (undifferentiated) arthritis (UDA) and early RA, efficacy of MT monotherapy and combined therapy, including, along with MT, the standard basic anti-rheumatic drugs (DMARDs) and genetically engineered biological drugs (GEBDs), the role of MT in the induction and maintenance of remission, including remission without treatment with GEBDs. A conclusion was drawn that administration of MT is required in all patients with early RA and probably in patients with UDA in case of high risk of the disease transformation into RA. Early administration of the subcutaneous form of MT improves the efficacy of RA treatment and should be a mandatory component of the intensive RA treatment strategies, regardless of the use of glucocorticoids and other standard DMARDs and GEBDs. In patients with high disease activity, who require administration of high dose of MT or different schemes of combined treatment, it is advisable to begin the treatment with the injectable form of MT rather than tablet one.